1637 : the Polish maelstrom - Flint, Eric (Ring of fire (Riverdale, N.Y.), 2019)
"The Ottoman Empire has captured Vienna and is now laying siege to the Austrian government in exile. Both the United States of Europe and the Kingdom of Bohemia have come to Austria's assistance but everyone knows it is going to be a long, brutal struggle. General Mike Stearns proposes opening up a second front in the Levant which the USE's emperor Gustavus Adolphus approves. Meanwhile, Poland is coming to a boil. Gretchen Richter, newly elected chancellor of Saxony has seized control of Lower Silesia and plans to form an alliance with the Polish revolutionaries. And the Bohemians send an army led by Morris Roth to aid them as well. Additionally, Mike Stearns send an army division under the command of Jeff Higgins to reinforce his wife Gretchen in Silesia. The maelstrom grows. Will it drag all the displaced Americans and their allies down with it?"--